Identification of antioxidants in young mango leaves by LC-ABTS and LC-MS - Prommajak T. (Chiang Mai University, 2014)
Thai eat the young leaves of mango as vegetables. Antioxidants in young leaves of mango cultivars 'Talapnak', 'Chok Anan' and 'Nam Dok Mai' were identified by high-performance liquid chromatography coupled with an online ABTS assay (HPLC-ABTS) and electrospray ionization mass spectrometer (HPLC-ESI-MS). Young leaves of mango cv. 'Nam Dok Mai' had the highest antioxidant capacity. Major antioxidants in young mango leaves were mangiferin and benzophenones (maclurin and iriflophenone derivatives). Mangiferin presented in higher quantities than other compounds in each cultivar, with cv. 'Talapnak' containing the most (37.92±0.98 mg/g DW). The compound with the highest antioxidant capacity in all cultivars was mangiferin pentoside (from 1.19±0.25 mmol TE/g DW in cv. 'Chok Anan' to 2.13±0.04 mmol TE/g DW in cv. 'Talapnak'). The compound with the highest Trolox equivalent antioxidant capacity was maclurin galloyl glucoside (1.75±0.62 mol TE/mol).